The Role of Health Literacy in Protecting Children and Adolescents from Health Risks in the Context of the COVID-19 Pandemic [Rola wiedzy o zdrowiu w ochronie dzieci i młodzieży przed zagrożeniami zdrowotnymi w kontekście pandemii COVID-19] - Leksy, Karina; Borzucka-Sitkiewicz, Katarzyna (Studia Edukacyjne, 2021)
Governments all over the world have taken unparalleled measures to combat the spread of the co[1]ronavirus. Severe restrictions have been imposed, reducing face-to-face contact where possible. This situation seems to be particularly acute for children and youth, who may not understand the orders and bans. Many studies analyzed in this paper have provided evidence that children’s and adole[1]scents’ health has been negatively affected within the last months due to school closures and the need for social and physical distancing because of the coronavirus. Adults should be aware of children’s and adolescents’ difficulties and support them during this unique time. In the face of serious threats currently emerging due to COVID-19, health promotion is essential, as people regain control of their health, protect themselves and manage the potential consequences of the disease. The schools are faced with a huge task of promoting health, preparing students to cope with difficult and uncertain situations, including strengthening their health literacy. Health literacy, which is a set of skills, varies from individual to individual, which means that interventions in this area should focus on improving people’s skills and capacities through educational activities, discussed in this article.